Formulation of mouth rinse from the essential oils of lime (Citrus aurantifolia) and its inhibitory efficacy on the growth of Streptococcus mutans – in vitro - Mulyanti, Sri; Laela, Dewi Sodja; Julaeha, Euis; Suwargiani, Anne Agustina; Aripin, Dudi (Padjadjaran Journal of Dentistry, 2020)
Introduction: Essentials oil of lime (Citrus aurantifolia) peel has high activity in inhibiting the growth of Streptococcus mutans bacteria. The objective of this research was to determine the formulation of mouth rinse from the essential oils of lime (C. aurantifolia) with the highest inhibitory and on the growth of S. mutans. Methods: This research was an experimental in-vitro study. The sample used was the lime (C. aurantifolia) peel waste peel using hydrodistillation technique; testing of the essential oil quality was performed using 100°C distilled water for 3 hours; organoleptic test and physical mouth rinse formula test was also conducted. Mouth rinse formulations were made from the essential oils in the concentrations of 1, 2, 4, 8, 10, and 20%. Mouth rinse activity was tested with optical density. Minimum inhibitory concentration was determined with microdilution. Results: Essential oil mouth rinse formulation showed antibacterial activity at the concentrations of 2, 4, 8, 10, and 20% (formulations I-IV); the recommended mouth rinse concentration was 4% (formulation III) due to its highest antibacterial. Formulation IV showed the highest minimum inhibitory concentration value of 5.2 mg/mL (0.52%) and the safe minimum bactericidal concentration of 0.4 mg/mL (1.04). Conclusion: Mouth rinse formulation from essential oils of lime (C. aurantifolia) peel begins to show inhibition of the growth of S. mutans bacteria at the concentration of 2% essential oils (formulation II), with inhibition against the growth of S. mutans is 7.08. The formula shows a minimum inhibitory concentration (MIC) value and a minimum bactericidal concentration (MBC) of 5.2 mg/mL (0.52%) and 10.4 mg/mL (1.04), respectively.